Multifractal analyses on the retention mechanism of fracturing fluid in tight sandstone - Yan Zhang; Zhiping Li; Hao Wu (Unconventional Resources, 2025)
Tight sandstone is defined by its low porosity, limited permeability, and considerable heterogeneity, necessitating hydraulic fracturing for hydrocarbon extraction. However, fracturing fluid often becomes retained within the reservoir, which can markedly reduce hydrocarbon extraction efficiency. The mechanisms behind this retention in tight sandstone remain unclear. In this study, we employed the centrifugation method to replicate the flowback and retention processes of fracturing fluid. We conducted low-pressure nitrogen gas adsorption (LP-N2GA) experiments, nuclear magnetic resonance (NMR) analysis, and utilized combined multifractal methods to examine the alterations in pore structure and fluid distribution properties of sandstone samples. The LP-N2GA experiments revealed that after fracturing fluid treatment, the surface area and pore volume of the samples diminished, whereas the average pore size expanded, and the pore size distribution range narrowed. Multifractal analysis indicated that post-treatment, the number of clustered pores decreased, pore connectivity improved, and distribution of pore sizes became more homogeneous. NMR experiments showed that during pressure-driven imbibition, fracturing fluid primarily occupied large pores, and at high imbibition pressures, the fluid within these large pores was more easily recovered. Conversely, in small pores, fracturing fluid was more likely to flowback under lower imbibition pressures. Further multifractal analysis demonstrated that with increasing flowback pressure, the connectivity of trapped fracturing fluid within the pores gradually deteriorates, while the clustering and distribution of the fluid initially decreased and then increased. These findings provide deeper insights into the mechanisms governing the fluid distribution changes during the fracturing fluid flowback process in tight sandstone.